Spontaneous sweating thermal barrier composite coating and preparation method thereof

By applying multi-variable rare earth oxide composite stable zirconia ceramic material and nickel-coated copper spontaneous heat barrier composite coating on the surface of the aircraft, the problems of high density and uneven pore structure of existing sweat cooling materials are solved, and efficient Thermal barrier insulation and cooling effects meet the lightweight and high-temperature protection needs of the aircraft.

CN119162531APending Publication Date: 2024-12-20XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411474720.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing sweat cooling materials have high density and low mechanical strength, which cannot meet the lightweight needs of aircraft. Moreover, the porous materials of traditional sweat structures have uneven porous structures, resulting in local hot spots and low cooling efficiency.

Method used

Using spontaneous sweating heat barrier composite coating, including bonding layer, thermal barrier layer and sweating heat barrier layer, multi-component rare earth oxide composite stable zirconia ceramic material and nickel-coated copper as metal perspirants, formed through high-energy plasma spraying technology Gradient structure to improve the bond strength and thermal insulation properties of the coating.

Benefits of technology

It achieves the high temperature resistance, ablation and thermal insulation properties of the coating, extends life, and improves cooling efficiency without increasing the structural weight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162531A_ABST
    Figure CN119162531A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coating materials, in particular to a spontaneous perspiration thermal barrier composite coating and a preparation method thereof. The spontaneous sweating thermal barrier composite coating comprises a bonding layer, a thermal barrier layer and a sweating thermal barrier layer which are arranged in a stacked mode. The bonding layer comprises NiCoCrAlY and / or NiCoCrAlYX, and X is selected from one or more of Hf, Si and Ta; the thermal barrier layer is made of a composite ceramic material, the composite ceramic material is a multi-element rare earth oxide composite stable zirconia ceramic, and rare earth elements in the multi-element rare earth oxide are any two or more of La, Ce, Sc, Gd, Dy, Y or Yb; the sweating thermal barrier layer comprises the composite ceramic material and a metal sweating agent, and the metal sweating agent is Cu or Ni coated Cu metal micro powder. The spontaneous sweating thermal barrier composite coating provided by the invention has high bonding strength and excellent heat insulation and ablation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of coating materials, and in particular to a self-sweating thermal barrier composite coating and a preparation method thereof. Background Art

[0002] The sweating material is a sweating cooling composite material composed of high melting point ceramics or metals and low melting point and low boiling point metals. It has the characteristics of high specific strength, high temperature resistance, erosion resistance, thermal shock resistance, and ablation resistance. It is a highly promising next-generation new high temperature resistant material. It has important application prospects in high temperature components in aerospace, such as rocket nozzles, air rudders, and nose cones, high temperature resistant electrical contacts in industry, such as high voltage and high power electrical switch contacts, and many other fields.

[0003] At present, the sweating cooling materials are mainly composite metal or ceramic materials with tungsten infiltrated copper, high temperature resistant TiB2 ceramics, etc. as the skeleton. The density of the material is relatively large (W-Cu even reaches 17g / cm 3 The use of titanium alloy and aluminum alloy to reduce the weight of heat-resistant parts such as air rudders has made it difficult for their ablation resistance and high-temperature strength to meet the actual use requirements. Therefore, it is urgent to develop new lightweight ablation-resistant materials or coatings to meet the needs of high Mach number engines, reduce structural weight, reduce material costs and improve heat resistance.

[0004] In the existing sweating cooling preparation technology, the composite sweating materials prepared by laser additive manufacturing, cold isostatic pressing and high-temperature vacuum sintering have high density and low mechanical strength, which cannot meet the requirements of lightweight aircraft. In addition, the pore structure of the traditional sweating structure porous material is uneven, and when the aircraft surface is subjected to uneven heat load, local hot spots will appear. The non-uniformly distributed pore structure exacerbates the steam blocking effect, resulting in local high temperature that is difficult to eliminate with the increase of the sweating agent phase change cooling. In addition, the low permeability and thermal conductivity of the ceramic-based composite material will also lead to problems such as low sweating agent phase change ratio and reduced cooling efficiency.

[0005] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0006] The purpose of the present disclosure is to provide a self-sweating thermal barrier composite coating and a preparation method thereof, aiming to improve the thermal insulation and ablation resistance performance of the ultra-high temperature thermal barrier coating.

[0007] Other features and advantages of the present disclosure will become apparent from the following detailed description, or may be learned in part by the practice of the present disclosure.

[0008] According to one aspect of an embodiment of the present disclosure, a self-sweating thermal barrier composite coating is provided, comprising: a stacked bonding layer, a thermal barrier layer and a sweating thermal barrier layer; the bonding layer comprises NiCoCrAlY and / or NiCoCrAlYX, wherein X is selected from one or more of Hf, Si and Ta; the thermal barrier layer is a composite ceramic material, the composite ceramic material is a multinary rare earth oxide composite stabilized zirconia ceramic, the rare earth elements in the multinary rare earth oxide are any two or more of La, Ce, Sc, Gd, Dy, Y or Yb; the sweating thermal barrier layer comprises the composite ceramic material and a metal sweating agent, and the metal sweating agent is Cu or Ni-coated Cu metal powder.

[0009] According to some embodiments of the present disclosure, based on the aforementioned scheme, when the metal sweating agent is Ni-coated Cu metal micropowder, the mass ratio of Ni to Cu is 5-25:95-75, and the particle size is 30-60 μm.

[0010] According to some embodiments of the present disclosure, based on the aforementioned scheme, the mass fraction of the composite ceramic material gradually decreases from 100% and is not less than 55%; the mass fraction of the Ni-coated Cu metal powder gradually increases from 0% and is not higher than 45%.

[0011] According to some embodiments of the present disclosure, based on the aforementioned scheme, the thickness of the bonding layer is 50-100 μm, and the porosity is less than 3%; the thickness of the thermal barrier layer is 200-500 μm, and the porosity is less than 6%; the thickness of the sweating thermal barrier layer is 200-500 μm, and the porosity is 10%-25%.

[0012] According to some embodiments of the present disclosure, based on the aforementioned solution, the bonding strength of the self-sweating thermal barrier composite coating is 30-40 MPa.

[0013] According to a second aspect of an embodiment of the present disclosure, a method for preparing a self-sweating thermal barrier composite coating is provided, comprising: spraying a bonding layer powder on the surface of an alloy substrate by high-energy plasma spraying technology to form a bonding layer; spraying a thermal barrier layer powder on the surface of the bonding layer by high-energy plasma spraying technology to form a thermal barrier layer; spraying a sweating thermal barrier layer powder on the surface of the thermal barrier layer by high-energy plasma spraying technology in a synchronous, ex-situ double powder feeding manner to form a sweating thermal barrier layer, so as to form a self-sweating thermal barrier composite coating.

[0014] According to some embodiments of the present disclosure, based on the aforementioned scheme, the process parameters of the synchronous ectopic double powder feeding are: as the number of spraying times increases, the powder feeding rate of the metal sweating agent powder increases from 0 to 8-30 g / min, and the mass fraction gradually increases from 0 to 9-45%; the powder feeding rate of the composite ceramic material powder decreases from 40-18 g / min to 8 g / min, and the mass fraction decreases from 100% to 91-55%.

[0015] According to some embodiments of the present disclosure, based on the aforementioned scheme, the process parameters of the high-energy plasma spraying technology are: the spray gun power is 40-46 kW, the gas flow rates of argon and hydrogen are 150-200 and 50-100 L / min respectively, the feed rate is 8-40 g / min, and the coating thickness is 200-500 μm.

[0016] According to some embodiments of the present disclosure, based on the aforementioned solution, the alloy matrix is ​​any one of a high-temperature alloy, stainless steel, an iron-based alloy, a copper-based alloy and an aluminum-based alloy.

[0017] According to some embodiments of the present disclosure, based on the aforementioned solution, the thickness ratio of the thermal barrier layer and the sweating thermal barrier layer is configured according to the service temperature and cooling requirements of the self-sweating thermal barrier composite coating.

[0018] The exemplary embodiments of the present disclosure may have some or all of the following beneficial effects:

[0019] In the technical solutions provided in some embodiments of the present disclosure, a sweating thermal barrier composite coating is prepared by combining thermal barrier coating technology and metal sweating technology. On the one hand, a multi-rare earth oxide composite stabilized zirconia ceramic material is used, which has better phase stability and sintering resistance and lower thermal conductivity than traditional YSZ ceramic materials. On the other hand, nickel-clad copper is used as a metal sweating agent to effectively improve the problem of poor wettability and compatibility between metal and ceramic, and achieve uniform and adjustable sweating agent distribution pores. Therefore, when the composite coating reaches a high temperature of several thousand degrees in an instant during service, the temperature of the substrate can be reduced by means of the evaporation heat absorption of the low-melting-point metal and the heat insulation of the thermal barrier coating. The sweating thermal barrier coating can be used to improve high temperature resistance, ablation resistance, thermal insulation performance and extend service life under the premise of low weight gain and without affecting the mechanical strength of the substrate.

[0020] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0022] Figure 1 This is a cross-sectional test photograph of the self-sweating thermal barrier composite coating prepared in Example 2 of the present disclosure;

[0023] Figure 2 This is a photograph of the self-sweating thermal barrier composite coating prepared in Example 2 of the present disclosure after ablation;

[0024] Figure 3 These are the XRD test results of the self-sweating thermal barrier composite coatings prepared in Examples 5, 6, and 7 of the present disclosure. DETAILED DESCRIPTION

[0025] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the examples set forth herein; rather, these embodiments are provided so that this disclosure will be more comprehensive and complete and will fully convey the concept of the example embodiments to those skilled in the art.

[0026] In addition, the described features, structures or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced without one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known methods, devices, implementations or operations are not shown or described in detail to avoid blurring the various aspects of the present disclosure.

[0027] The block diagrams shown in the accompanying drawings are merely functional entities and do not necessarily correspond to physically independent entities. That is, these functional entities may be implemented in software form, or in one or more hardware modules or integrated circuits, or in different networks and / or processor devices and / or microcontroller devices.

[0028] The flowcharts shown in the accompanying drawings are only exemplary and do not necessarily include all the contents and operations / steps, nor must they be executed in the order described. For example, some operations / steps can be decomposed, and some operations / steps can be combined or partially combined, so the actual execution order may change according to actual conditions.

[0029] The sweating material is a sweating cooling composite material composed of high melting point ceramics or metals and low melting point and low boiling point metals. It has the characteristics of high specific strength, high temperature resistance, erosion resistance, thermal shock resistance, and ablation resistance. It is a highly promising next-generation new high temperature resistant material. It has important application prospects in high temperature components in aerospace, such as rocket nozzles, air rudders, and nose cones, high temperature resistant electrical contacts in industry, such as high voltage and high power electrical switch contacts, and many other fields.

[0030] At present, the main sweating cooling materials are composite metal or ceramic materials with tungsten-infiltrated copper, high-temperature resistant TiB2 ceramics, etc. as the skeleton, and the density of the materials is relatively high (W-Cu even reaches more than 17g / cm3). The heat-resistant parts such as air rudders that use titanium alloys and aluminum alloys to reduce weight have difficulty in meeting the actual use requirements in terms of ablation resistance and high-temperature strength. Therefore, it is urgent to develop new lightweight ablation-resistant materials or coatings to meet the needs of high Mach number engines, reduce structural weight, reduce material costs and improve heat resistance.

[0031] In the existing sweating cooling preparation technology, the composite sweating materials prepared by laser additive manufacturing, cold isostatic pressing and high-temperature vacuum sintering have high density and low mechanical strength, which cannot meet the requirements of lightweight aircraft. In addition, the pore structure of the traditional sweating structure porous material is uneven, and when the aircraft surface is subjected to uneven heat load, local hot spots will appear. The non-uniformly distributed pore structure exacerbates the steam blocking effect, resulting in local high temperature that is difficult to eliminate with the increase of the sweating agent phase change cooling. In addition, the low permeability and thermal conductivity of the ceramic-based composite material will also lead to problems such as low sweating agent phase change ratio and reduced cooling efficiency.

[0032] In view of the problems existing in the prior art, the present invention provides a self-sweating thermal barrier composite coating with integrated anti-ablation, heat insulation and heat protection and a spraying preparation method thereof, which can meet the critical thermal protection needs of high-speed aircraft during ultra-high-speed flight and improve its service stability in complex heat flow environments.

[0033] The present disclosure provides a self-sweating thermal barrier composite coating, comprising a stacked bonding layer, a thermal barrier layer and a sweating thermal barrier layer (also referred to as a gradient sweating thermal barrier layer).

[0034] Preferably, the bonding layer comprises NiCoCrAlY and / or NiCoCrAlYX, wherein X is selected from one or more of Hf, Si and Ta.

[0035] Preferably, the thermal barrier layer is a composite ceramic material, the composite ceramic material is a multi-component rare earth oxide composite stabilized zirconia ceramic, and the rare earth elements in the multi-component rare earth oxide are any two or more of La, Ce, Sc, Gd, Dy, Y or Yb.

[0036] The multi-rare earth oxide composite stabilized zirconia ceramic material has better phase stability, sintering resistance and lower thermal conductivity compared with traditional YSZ ceramic materials.

[0037] Preferably, the sweating thermal barrier layer comprises the composite ceramic material and a metal sweating agent, and the metal sweating agent is Cu or Ni-coated Cu metal powder.

[0038] Wherein, when the metal sweating agent is Ni-coated Cu metal powder (hereinafter referred to as Ni@Cu), the Ni coating layer can be prepared on the Cu surface by electroplating, chemical plating or physical vapor deposition. Preferably, the mass ratio of Ni to Cu after coating is 5-25:95-75, and the particle size is 30-60 μm.

[0039] Ni@Cu nickel-coated copper as a metal sweating agent can effectively improve the poor wettability and compatibility between metals and ceramics, and achieve uniform and adjustable sweating agent distribution pores.

[0040] In the present disclosure, the mass fraction of the composite ceramic material gradually decreases from 100% and is not less than 55%; the mass fraction of the Ni-coated Cu metal powder gradually increases from 0% and is not higher than 45%.

[0041] The gradient-changing composite structure facilitates the introduction of heat flow from the outer surface into the inner wall surface more easily. At the same time, a thermal barrier insulation layer is provided so that the composite coating can further improve the protection of the substrate through the heat exchange effect of sweating cooling while having certain thermal insulation performance.

[0042] In the present disclosure, the thickness of the bonding layer is 50-100 μm, and the porosity is less than 3%; the thickness of the thermal barrier layer is 200-500 μm, and the porosity is less than 6%; the thickness of the sweating thermal barrier layer is 200-500 μm, and the porosity is 10%-25%.

[0043] In the present disclosure, the bonding strength of the self-sweating thermal barrier composite coating is 30-40 MPa.

[0044] In addition, the present disclosure also discloses a method for preparing a self-sweating thermal barrier composite coating, which aims to prepare the self-sweating thermal barrier composite coating as mentioned above, comprising: spraying the powder of the bonding layer on the surface of the alloy substrate by high-energy plasma spraying technology to form a bonding layer; spraying the powder of the thermal barrier layer on the surface of the bonding layer by high-energy plasma spraying technology to form a thermal barrier layer; spraying the powder of the sweating thermal barrier layer on the surface of the thermal barrier layer by high-energy plasma spraying technology through synchronous ectopic double powder feeding to form a sweating thermal barrier layer, so as to form a self-sweating thermal barrier composite coating.

[0045] The sweating thermal barrier composite coating is prepared by combining thermal barrier coating technology with metal sweating technology. The porous skeleton matrix is ​​made of high-melting-point YSZ ceramics, and the gaps in the skeleton are filled with low-melting-point metals. During service, the composite coating reaches a temperature of several thousand degrees in an instant. With the help of the low-melting-point metal evaporation heat absorption and the thermal insulation of the thermal barrier coating, the temperature of the substrate is reduced. Under the premise of low weight gain and no impact on the mechanical strength of the substrate, the high-temperature resistance, ablation resistance, and thermal insulation performance are improved, and the service life is extended. The sweating thermal barrier coating has higher thermal insulation and cooling efficiency, and the preparation process is less time-consuming and more efficient. It can be used to prepare the high-temperature resistant coating on complex thrust components.

[0046] In the present disclosure, the process parameters of the synchronous ectopic dual powder feeding are: as the number of spraying increases, the powder feeding rate of the metal sweating agent powder increases from 0 to 8-30 g / min, and the mass fraction gradually increases from 0 to 9-45%, and the powder feeding rate of the composite ceramic material powder decreases from 40-18 g / min to 8 g / min, and the mass fraction decreases from 100% to 91-55%. Thus, a sweating thermal barrier layer with a continuous gradient is prepared.

[0047] The preparation is done by synchronous heterogeneous double powder feeding high energy plasma spraying technology, which avoids the difference in melting point of raw material powder, resulting in over-melting of low melting point material and insufficient melting of high melting point material. The gradient structure of sweating thermal barrier coating is achieved by continuous change of the feeding amount of YSZ and Ni@Cu metal materials. The spraying process does not require powder replacement, and the composite preparation of high / low melting point heterogeneous materials is achieved in one step, which effectively relieves the interlayer stress of multiple interfaces and significantly improves the coating quality. The coolant is transported in the YSZ skeleton structure to ensure continuous sweating and achieve efficient cooling.

[0048] In the present disclosure, the process parameters of the high-energy plasma spraying technology are: the spray gun power is 40-46kW, the gas flow rates of argon and hydrogen are 150-200 and 50-100L / min respectively, the feed rate is 8-40g / min, and the coating thickness is 200-500μm.

[0049] In the present disclosure, the alloy substrate is any one of high temperature alloy, stainless steel, iron-based alloy, copper-based alloy and aluminum-based alloy. In other words, the alloy substrate is not limited to high temperature alloy or stainless steel, and can be expanded to other alloy substrates such as copper-based and aluminum-based due to its excellent thermal insulation performance.

[0050] In the present disclosure, the thickness ratio of the thermal barrier layer and the sweating thermal barrier layer is configured according to the service temperature and cooling requirement of the self-sweating thermal barrier composite coating.

[0051] The technical advantages of the self-sweating thermal barrier composite coating provided by the present disclosure are illustrated below through specific embodiments.

[0052] Example 1

[0053] (1) NiCoCrAlY alloy bonding powder with a particle size of 50±20 μm, (La2O3, Y2O3)-ZrO2 rare earth oxide composite stabilized zirconia ceramic powder, and Ni-coated Cu powder with a mass ratio of 25 / 75 were selected as the original spray powders, and the powders were dried in an oven at 120°C before spraying;

[0054] (2) sandblasting the aluminum alloy substrate to be sprayed to roughen it to ensure that the spray coating can be firmly attached to the workpiece;

[0055] (3) spraying a bonding layer on the surface of the alloy substrate by high-energy plasma spraying. The process parameters of the high-energy plasma spraying in this step are as follows: a spray gun power of 45 kW, a spray gun distance of 120 mm, a gas flow rate of argon and hydrogen of 100 and 15 L / min, respectively, a feed rate of 20 g / min, a spray gun speed of 300 mm / s, and a spray thickness of 80 μm;

[0056] (4) preparing a thermal barrier layer on the surface of the bonding layer by high-energy plasma spraying. The process parameters of the plasma spraying in this step are as follows: a spray gun power of 60 kW, a spray gun distance of 120 mm, gas flow rates of argon and hydrogen of 150 and 20 L / min, respectively, a feed rate of 30 g / min, a spray gun speed of 300 mm / s, and a spray thickness of 300 μm;

[0057] (5) Spraying a gradient transition heat-generating thermal barrier layer, the metal heat-generating powder and the ceramic powder are fed separately in a synchronous and dys-situ manner, the metal heat-generating powder is fed into the low-temperature zone of the plasma jet, and the heat-generating thermal barrier layer is sprayed on the surface of the thermal barrier layer by continuously changing the feeding amount of the ceramic powder and the alloy bonding powder. The process conditions of the high-energy plasma spraying technology are: the spraying power is 50kW, the spray gun distance is 120mm, the main gas flow rate is 120L / min, the hydrogen flow rate is 15L / min, the metal heat-generating powder feeding rate increases from 0 to 40g / min, and as the number of spraying passes increases, the ceramic powder feeding rate decreases from 30g / min to 8g / min. As the number of spraying passes decreases, a heat-generating thermal barrier coating with a continuous gradient is prepared. The spray gun speed is 300mm / s, and the spraying thickness is 300μm.

[0058] Example 2

[0059] NiCoCrAlY alloy bonding powder with a particle size of 50±20μm, (La2O3, Y2O3)-ZrO2 rare earth oxide composite stabilized zirconia ceramic powder, and single Cu powder were selected as the original spray powder. The powder was dried in an oven at 120°C before spraying. The coating preparation process was consistent with that in Case 1.

[0060] Comparative Example 1

[0061] NiCoCrAlY alloy bonding powder with a particle size of 50±20 μm and (La2O3, Y2O3)-ZrO2 rare earth oxide composite stabilized zirconia ceramic powder were selected, and no metal sweating agent was used. During the spraying process, the bonding layer and the thermal barrier layer remained consistent with those in Example 1, but the thickness of the thermal barrier layer was the sum of the thermal barrier layer and the sweating thermal barrier layer in Example 1.

[0062] The Example 1, the Example 2 and the Comparative Example 1 were respectively subjected to strength tests to obtain the bonding strength of the coating, and the thermal insulation temperature test was performed to obtain the thermal insulation cooling gradient.

[0063] Among them, the bonding strength test is based on GB / T 8642-2002 standard, and is tested by a universal tensile testing machine. The maximum load is divided by the cross-sectional area to obtain the coating bonding strength. In the thermal insulation temperature test, the coating surface is heated to 1800℃ within 20s by an acetylene + oxygen spray gun, and the coating surface temperature is tested by an infrared tester. After keeping the temperature at 1800℃ for 20s, the back temperature of the alloy is tested by a thermocouple at the same time. The difference is the thermal insulation cooling gradient.

[0064] The bonding strength of the self-sweating thermal barrier composite coating prepared in Example 1 is 30 MPa, and the thermal insulation temperature gradient is 550° C. The bonding strength of the coating prepared in Example 2 is 25 MPa, and the thermal insulation temperature gradient is 400° C. The bonding strength of the coating prepared in Comparative Example 1 is 35 MPa, and the thermal insulation temperature gradient is 300° C.

[0065] Comparing Examples 1 and 2 with Comparative Example 1, the difference is that Comparative Example 1 does not use Ni-coated Cu metal sweating agent, while Example 1 uses a metal sweating agent with a specific mass fraction, and Example 2 uses a pure Cu metal sweating agent. From the thermal insulation and cooling gradient index data, the thermal insulation and heat protection effect of adding the gradient self-sweating thermal barrier composite coating is significantly improved. Compared with Comparative Example 1, the thermal insulation temperature of Example 1 is increased from 300°C to 550°C, and the high bonding strength>30MPa is still maintained. Compared with Comparative Example 1, although the bonding strength of Example 2 is reduced, the thermal insulation temperature is increased from 300°C to 400°C. This is because the metal sweating agent vaporizes and evaporates at high temperature to take away the heat of the substrate, thereby greatly reducing the temperature of the back of the substrate.

[0066] Embodiments 3 to 5

[0067] In order to explore the effects of metal sweating agents with different parameters on the thermal insulation cooling gradient, Examples 3 to 5 are involved.

[0068] The difference between the preparation process of Examples 3-5 and Example 1 is that different bonding layers, different rare earth oxide composite stabilized zirconia ceramic powders, and Ni@Cu powders coated with different mass ratios are used to obtain each layer of coating with material components. In addition, the thickness, porosity, bonding strength and thermal insulation cooling gradient of each layer of coating are also different, and the specific parameters are shown in Table 1.

[0069] Table 1 Parameters of self-sweating thermal barrier composite coatings of Examples 1-4

[0070]

[0071] As shown in Reference Table 1, Examples 1 and 3 to 5 all use metal sweating agents. Compared with Comparative Example 1, the thermal insulation temperature gradient still performs well, increasing from 300°C to 550-575°C, and still maintains a relatively high bonding strength of >30MPa, which further confirms that the self-sweating thermal barrier composite coating provided by the present disclosure has high bonding strength and excellent thermal insulation and heat protection properties.

[0072] The difference between Examples 1 and 3 to 5 is that metal sweating agents with different Ni / Cu mass ratios are used. As the Cu ratio increases, the sweating cooling effect gradually increases. However, when the Ni ratio is greatly reduced, the wettability and compatibility of the metal and ceramic are poor, and the metal sweating agent is unevenly distributed in the coating, resulting in a decrease in the thermal insulation effect as the sweating agent content increases.

[0073] Figure 1 This is a cross-sectional test photograph of the self-sweating thermal barrier composite coating prepared in Example 3 of the present disclosure. Figure 1 As shown, the self-sweating thermal barrier composite coating includes a base material, a bonding layer, a thermal barrier layer and a gradient sweating thermal barrier layer. The interfaces between the layers in the coating are tightly bonded, and an alternating bite bonding surface is formed between the ceramic layer and the bonding layer.

[0074] Figure 2 The self-sweating thermal barrier composite coating prepared in Example 3 of the present disclosure after ablation. The self-sweating thermal barrier composite coating prepared on the surface of the aluminum alloy in Example 2 was ablated at 1800°C. Figure 2 As shown, the coating did not fail and the aluminum alloy substrate did not deform.

[0075] Embodiments 6 to 10

[0076] Examples 6 to 10 use the same bonding layer materials, thermal barrier ceramic powders and metal sweating agents as Example 1, but differ in the preparation process parameters of the sweating thermal barrier layer, as shown in Table 2 for details.

[0077] Table 2 Preparation process parameters of sweating thermal barrier layer in Examples 6 to 10

[0078]

[0079] The difference between Examples 6 to 10 lies in the different preparation process parameters, among which the power and gas flow rate directly affect the temperature and melting degree of the powder particles, and thus affect the microstructure and performance of the coating. As can be seen from Table 2, the porosity of the coating changes significantly, and the ceramic coating with higher porosity has better thermal insulation performance, but it may also cause the coating bonding strength to decrease. This is because the pores weaken the continuity inside the material and reduce the overall strength of the coating.

[0080] At the same time, by adjusting the feeding rate of the sweating agent and ceramic powder, the mass ratio of ceramic and sweating agent in the sweating thermal barrier layer is adjusted to obtain a good combination performance and good thermal insulation performance, and the sweating agent mass ratio is controlled within a moderate range. Because when the sweating agent ratio is small, a continuous sweating liquid phase cannot be formed in the coating, and when exposed to high temperature, local hot spots will be caused, resulting in steam blockage, which is not conducive to improving thermal insulation performance. When it is within a moderate range, it is more conducive to forming a gaseous heat-absorbing insulation layer with large heat capacity and low thermal conductivity, ensuring continuous sweating.

[0081] Combining Table 1 and Table 2, it can be seen that the sweating thermal barrier coating designed and prepared in the present invention has the characteristics of high bonding strength (bonding strength is greater than 30MPa) and excellent thermal insulation and heat protection performance (the maximum insulation temperature reaches 600°C), and can be used as a new type of thermal barrier coating on the surface of low-melting point and low-density alloy substrates such as aluminum alloys and titanium alloys.

[0082] Figure 3 The XRD test results of the self-sweating thermal barrier composite coatings prepared in Examples 6, 7, and 8 of the present disclosure are shown in FIG. Figure 3 As shown in the figure, with the increase of the proportion of the spraying sweating agent, the cubic phase or metastable tetragonal phase YSZ in the coating gradually decreases, the proportion of the Cu single phase gradually increases, and some copper oxides are generated.

[0083] Through the above embodiments, the purpose of the present invention is fully and effectively achieved. Those skilled in the art can understand that the present invention includes but is not limited to the contents described in the drawings and the above specific embodiments. Although the present invention has been described with respect to the most practical and preferred embodiments currently considered, it should be understood that the present invention is not limited to the disclosed embodiments, and any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.

[0084] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. The present disclosure is intended to cover any variations, uses or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure.

[0085] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A self-sweating thermal barrier composite coating, characterized in that: include: A stacked adhesive layer, a thermal barrier layer and a sweating thermal barrier layer; The bonding layer comprises NiCoCrAlY and / or NiCoCrAlYX, wherein X is selected from one or more of Hf, Si and Ta; The thermal barrier layer is a composite ceramic material, the composite ceramic material is a multi-component rare earth oxide composite stabilized zirconia ceramic, and the rare earth elements in the multi-component rare earth oxide are any two or more of La, Ce, Sc, Gd, Dy, Y or Yb; The sweating thermal barrier layer comprises the composite ceramic material and a metal sweating agent, and the metal sweating agent is Cu or Ni-coated Cu metal powder.

2. The self-sweating thermal barrier composite coating according to claim 1, characterized in that: When the metal sweating agent is Ni-coated Cu metal fine powder, the mass ratio of Ni to Cu is 5-25:95-75, and the particle size is 30-60 μm.

3. The self-sweating thermal barrier composite coating according to claim 1, characterized in that: The mass fraction of the composite ceramic material gradually decreases from 100% and is not less than 55%; the mass fraction of the Ni-coated Cu metal powder gradually increases from 0% and is not higher than 45%.

4. The self-sweating thermal barrier composite coating according to claim 1, characterized in that: The thickness of the bonding layer is 50-100 μm, and the porosity is less than 3%; the thickness of the thermal barrier layer is 200-500 μm, and the porosity is less than 6%; the thickness of the sweating thermal barrier layer is 200-500 μm, and the porosity is 10%-25%.

5. The self-sweating thermal barrier composite coating according to claim 1, characterized in that: The bonding strength of the self-sweating thermal barrier composite coating is 30-40 MPa.

6. A method for preparing a self-sweating thermal barrier composite coating according to any one of claims 1 to 5, characterized in that: include: The bonding layer powder is sprayed on the surface of the alloy substrate by high-energy plasma spraying technology to form a bonding layer; The thermal barrier layer powder is sprayed on the surface of the bonding layer by high energy plasma spraying technology to form the thermal barrier layer; The powder of the sweating thermal barrier layer is sprayed on the surface of the thermal barrier layer by a synchronous ectopic double powder feeding method using a high-energy plasma spraying technology to form a sweating thermal barrier layer, so as to form a self-sweating thermal barrier composite coating.

7. The method for preparing a self-sweating thermal barrier composite coating according to claim 6, characterized in that: The process parameters of the synchronous ectopic double powder feeding are: As the number of spraying times increases, the powder feeding rate of the metal sweating agent powder increases from 0 to 8-30 g / min, and the mass fraction gradually increases from 0 to 9-45%. The powder feeding rate of the composite ceramic material powder decreases from 40-18 g / min to 8 g / min, and the mass fraction decreases from 100% to 91-55%.

8. The method for preparing a self-sweating thermal barrier composite coating according to claim 6, characterized in that: The process parameters of the high energy plasma spraying technology are: The spray gun power is 40-46 kW, the gas flow rates of argon and hydrogen are 150-200 and 50-100 L / min respectively, the feed rate is 8-40 g / min, and the coating thickness is 200-500 μm.

9. The method for preparing a self-sweating thermal barrier composite coating according to claim 6, characterized in that: The alloy matrix is ​​any one of high temperature alloy, stainless steel, iron-based alloy, copper-based alloy and aluminum-based alloy.

10. The method for preparing a self-sweating thermal barrier composite coating according to claim 6, characterized in that: The thickness ratio of the thermal barrier layer and the sweating thermal barrier layer is configured according to the service temperature and cooling requirements of the self-sweating thermal barrier composite coating.

Citation Information

Cited By

  • Gradient composite coating as well as preparation method and application thereof

    CN122279453A